2000
DOI: 10.1074/jbc.m000163200
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein Receptors in Extraembryonic Tissues of the Chicken

Abstract: Yolk is the major source of nutrients for the developing chicken embryo, but molecular details of the delivery mechanisms are largely unknown. During oogenesis in the chicken, the main yolk components vitellogenin and very low density lipoprotein (VLDL) are taken up into the oocytes via a member of the low density lipoprotein receptor gene family termed LR8 (Bujo, H., Hermann, M., Kaderli, M. O., Jacobsen, L., Sugawara, S., Nimpf, J., Yamamoto, T., and Schneider, W. J. (1994) EMBO J. 13, 5165-5175). This endoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 50 publications
0
12
1
Order By: Relevance
“…Yolk VLDL contains apolipoprotein (apo) B fragments, cathepsin D-catalyzed intraoocytic proteolysis of apoB-100. In contrast, intact apoB-100, which is a major apo of VLDL in the hen, was present in the circulating VLDL of the embryo M. Sat0 and M. Furuse (Hermann et al, 2000). These data show that VLDL in the embryonic circulation seems to result from de nouo synthesis rather than directly from the yolk.…”
Section: Introductioncontrasting
confidence: 37%
See 2 more Smart Citations
“…Yolk VLDL contains apolipoprotein (apo) B fragments, cathepsin D-catalyzed intraoocytic proteolysis of apoB-100. In contrast, intact apoB-100, which is a major apo of VLDL in the hen, was present in the circulating VLDL of the embryo M. Sat0 and M. Furuse (Hermann et al, 2000). These data show that VLDL in the embryonic circulation seems to result from de nouo synthesis rather than directly from the yolk.…”
Section: Introductioncontrasting
confidence: 37%
“…In fact, the VLDL fraction provides Yolk VLDL binds t o the low density lipoprotein receptor (LDLR) family member termed LR8, which is expressed in the extraembryonic yolk sac and mobilizes yolk for utilization by the embryo. Stored yolk VLDL interacts with LR8 localized on the surface of the yolk sac endodermal endothelial cells and is internalized (Hermann et al, 2000). These results indicate that members of LDLR family play important roles in lipid metabolism and growth of the chicken embryo.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…The ligand binding domains of cubilin and LRP2 recognize a vast number of diverse proteins, many of which are yolk constituents, such as protein-bound vitamins, hormones, and a range of lipoproteins (28). Furthermore, we have previously shown that the YS EECs also express LR8 (the galline homologue of the mammalian VLDL receptor), which is capable of internalizing apoB-containing lipoproteins, such as VLDL (22), expanding the list of receptors involved in the uptake of yolk precursor macromolecules into the EECs.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that the O-linked domain may play an important role in the affinity between the receptors and their ligands. The role of VLDLR II in lipid metabolism was less obvious than for VLDLR I, and it is supposed to participate in other metabolic processes (Hermann et al 2000;May et al 2002May et al , 2003b. Their tissue expression pattern and capability to bind and internalize the lipoproteins of the two VLDLR subtypes indicate that the expression level of the two subtypes correspond to the activity of lipid metabolism in different tissues.…”
Section: Discussionmentioning
confidence: 99%